Faktor-Faktor yang Mempengaruhi Kinerja Pegawai: Kajian Literatur tentang Pengembangan SDM, Keterlibatan Kerja, dan Etos Kerja - Aris Nurmansah; Khuzaini; Zakky Zambrudi; Syahrial Shaddiq (PT. Hasba Edukasi Mandiri, 2026)
This study aims to examine the factors influencing employee performance from the perspectives of human resource development, work engagement, and work ethic using a literature review approach. The study is based on the analysis of eleven empirical articles obtained from open-access scientific journals, selected based on their relevance to the research variables. Data were analyzed using a descriptive method to identify patterns, relationships, and inconsistencies among previous studies. The findings indicate that human resource development does not consistently have a direct effect on employee performance, but rather influences performance through mediating variables such as organizational commitment and work ethic. Work ethic is identified as the most consistent and dominant factor affecting employee performance, as it reflects individual values, discipline, and work motivation. In addition, leadership and human resource management strategies play an important role in shaping a positive work ethic. Meanwhile, work engagement is conceptually significant in enhancing employee performance, although empirical evidence remains limited. These results suggest that employee performance is influenced by a complex interaction of structural, psychological, and behavioral factors, highlighting the importance of an integrative approach in human resource management to achieve sustainable performance improvement